From work-related stress evaluation to organizational wellbeing promotion: the case of an Italian pharmaceutical company - Emanuel, Federica; Molino, Monica; Ghislieri, Chiara; Ghini, Riccardo; Tortone, Alberto; Cortese, Claudio Giovanni (La Medicina del Lavoro, 2016)
Background: Work-related stress evaluation is a legal requirement for companies that, in some cases, might be seen as an opportunity to examine wellbeing at work and the dimensions related to it, through the involvement of employees. To that end, this study considers the job demands-resources model as a theoretical framework. Objectives: The study has a twofold objective: a) to describe the process of subjective evaluation carried out in the Italian plant of a pharmaceutical company; and b) to show and discuss results of the analyses performed on variables, examining in detail the relationship between two outcomes (job satisfaction and emotional exhaustion) and some job demands (workload and job effort), job resources (safety climate, clarity of roles, clarity and applicability of procedures, supervisor relational justice and colleague support), and personal resources (internal locus of control and job-related self-efficacy). Methods: The research was conducted through focus groups and a self-report questionnaire that involved all plant employees. Final respondents were 143 (85.1% of employees). Results: The regression model, with job satisfaction as a dependent variable, showed a positive relationship with some organizational resources: clarity of roles, clarity and applicability of procedures, supervisor relational justice and colleague support. The regression model, with emotional exhaustion as a dependent variable, showed a positive relationship with two job demands, workload and job effort, and a negative relationship with job-related self-efficacy. Conclusions: The study confirmed how important it is to consider wellbeing at work, in its cognitive and emotional dimensions, and its relationship with job demands and resources, within subjective evaluation of work-related stress. Starting from the study results, the research identified a plan of interventions designed for specific areas of improvement.